Corporate Political Connections and Tax Aggressiveness1. (1st July 2015) - Kim, Chansog (Francis); Zhang, Liandong
Abstract: This study investigates the relation between corporate political connections and tax aggressiveness. We study a broad array of corporate political activities, including the employment of connected directors, campaign contributions, and lobbying. Using a large hand‐collected data set of U.S. firms' political connections, we find that politically connected firms are more tax aggressive than nonconnected firms, after controlling for other determinants of tax aggressiveness, industry and year fixed effects, and the endogenous choice of being politically connected. Our findings are robust to various measures of political connections and tax aggressiveness. These results are consistent with the conjecture that politically connected firms are more tax aggressive because of their lower expected cost of tax enforcement, better information regarding tax law and enforcement changes, lower capital market pressure for transparency, and greater risk‐taking tendencies induced by political connections.